Targeting the Type II Secretion System: Development, Optimization, and Validation of a High-Throughput Screen for the Identification of Small Molecule Inhibitors - Waack, Ursula; Johnson, Tanya L.; Chedid, Khalil; Xi, Chuanwu; Simmons, Lyle A.; Mobley, Harry L. T.; Sandkvist, Maria (Frontiers in Cellular and Infection Microbiology, 2017)
Nosocomial pathogens that develop multidrug resistance present an increasing problem for healthcare facilities. Due to its rapid rise in antibiotic resistance, Acinetobacter baumannii is one of the most concerning gram-negative species. A. baumannii typically infects immune compromised individuals resulting in a variety of outcomes, including pneumonia and bacteremia. Using a murine model for bacteremia, we have previously shown that the type II secretion system (T2SS) contributes to in vivo fitness of A. baumannii. Here, we provide support for a role of the T2SS in protecting A. baumannii from human complement as deletion of the T2SS gene gspD resulted in a 100-fold reduction in surviving cells when incubated with human serum. This effect was abrogated in the absence of Factor B, a component of the alternative pathway of complement activation, indicating that the T2SS protects A. baumannii against the alternative complement pathway. Because inactivation of the T2SS results in loss of secretion of multiple enzymes, reduced in vivo fitness, and increased sensitivity to human complement, the T2SS may be a suitable target for therapeutic intervention. Accordingly, we developed and optimized a whole-cell high-throughput screening (HTS) assay based on secreted lipase activity to identify small molecule inhibitors of the T2SS. We tested the reproducibility of our assay using a 6,400-compound library. With small variation within controls and a dynamic range between positive and negative controls, the assay had a z-factor of 0.65, establishing its suitability for HTS. Our screen identified the lipase inhibitors Orlistat and Ebelactone B demonstrating the specificity of the assay. To eliminate inhibitors of lipase activity and lipase expression, two counter assays were developed and optimized. By implementing these assays, all seven tricyclic antidepressants present in the library were found to be inhibitors of the lipase, highlighting the potential of identifying alternative targets for approved pharmaceuticals. Although no T2SS inhibitor was identified among the compounds that reduced lipase activity by ≥30%, our small proof-of-concept pilot study indicates that the HTS regimen is simple, reproducible, and specific and that it can be used to screen larger libraries for the identification of T2SS inhibitors that may be developed into novel A. baumannii therapeutics.